English Learning Profiles of Non-English Major Students: A Comparative Study Between Accounting and Management Programs - Suherman, LaOde Achmad; Akfan, Sofyan Sukwara; Hamka, Nurhadi; Hasan, Aswiro; Riniati, Wa Ode; Arba’a, Nur Agniatmi (Institut Agama Islam Negeri Palopo, 2026)
This study investigates the English learning profiles of non-English major students, specifically those enrolled in Accounting and Management programs at a private university in Indonesia. A descriptive quantitative research design was employed involving 53 Students (24 Accounting, 29 Management), capturing students’ self-perceived English proficiency, learning barriers, motivations, learning preferences, and strategies. The findings indicate generally low self-perceived English proficiency across both groups, with 58.3% of Accounting students and 75.9% of Management students classifying themselves at the beginner level.. The study identified common learning barriers such as limited vocabulary, technical challenges (e.g., grammar and pronunciation), and a lack of supportive learning environments. In terms of motivation, Management students exhibited a stronger focus on global communication, while Accounting students prioritized career-related goals. Both groups favored informal and interactive learning strategies, with a preference for watching English-language films, using language learning applications, and practicing with peers. These findings suggest incorporating informal digital learning tools, such as language learning applications and audiovisual media, alongside peer-supported collaborative activities into ESP curricula to better align instruction with students’ demonstrated learning preferences.